Efektivitas Nilai Specific Gravity Larutan Kalsium Karbonat (CaCo3) untuk Meminimalisir Losses Claybath - Ahmad Mahfud (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
Research aims to understand large percentage kernels losses claybath, conform to established standards of pks rhs and the effectiveness of value specific gravity solution of calcium carbonate (CaCO3) as the process of separation kernels and shell .Research carried out by analyzing capacity bait in and analysis kernels losses after checking value specific gravity.The study was carried out with the methods study literature, deksriptif analysis and the reckoning analysis the quality of the nucleus palm . Methods used in data collection adhering to a standard operating procedures the sample collection output claybath and capacity bait claybath. Sample is taken directly, were analysed with the methods analysis core palm oil. Based on an analysis done, drawn conclusion solution CaCO3 having a level saturation, if bait entering claybath large, so solution CaCO3 will quickly saturated caused by oil contained in kernels, The effectiveness of value sg in solution claybath found in SG 1.16 with the kernel losses 1.97 % to sample or 0.02 % to FFB and kernel dirt content 6.91 %.